Communicating Science With YouTube Videos: How Nine Factors Relate to and Affect Video Views - Velho, Raphaela Martins; Mendes, Amanda Merian Freitas; Azevedo, Caio Lucidius Naberezny (Frontiers in Communication, 2020)
Recent works about science communication through online videos on YouTube have focused mostly on categorization, content description, and the video's approach to scientific themes. However, still little is known about factors affecting science video popularity on the platform. This study aims to describe the relationship between nine content-related and content-agnostic factors, and the popularity of science videos on YouTube, defined as the number of views per days since the video posting. We collected a sample of 441 semi-randomly selected videos produced by the ScienceVlogs Brasil project – a Brazilian alliance of science channels hosted by independent science communicators on YouTube. Content-related factors were video theme, video format and video editing features, while content-agnostic factors were video length, video age, channel productivity, number of likes, number of comments and channel to which the video belongs. Descriptive and inferential analyses were performed with the R software to assess the correlation of each factor with the popularity of each video. Descriptive results show that the most popular science videos are those with interdisciplinary themes, styled either as vlog, animation or group conversation, and those belonging to the channels “Ciência Todo Dia”, “Minuto da Terra”, “Canal do Pirula” e “Papo de Biólogo”. The inferential analysis shows that the most relevant factors to predict popularity, according to our model, are number of likes per video, channel productivity, video age and video format.